2008
DOI: 10.1002/clen.200700190
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Use of Reclaimed Water on the Quality of Groundwater Resources in the Jordan Valley, Jordan

Abstract: The use of reclaimed water and its impact on groundwater quality in the middle and southern parts of the Jordan Valley are investigated. The chemical analyses indicate that nitrate and bacteriological pollution is widespread, and thus, seriously affects groundwater use. During the study, 365 water samples were collected from wells and springs to determine the water chemistry and the extent of nitrate pollution. Three hydrochemical facies are identifed, i. e., (Ca -(Mg) -Na -HCO 3 ), (Ca -Na -SO 4 -Cl) and (Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Fruit trees and palms are grown in the Al Remal and Muaddi areas. Soil texture in the study area is mainly clay loam, loam, silt loam, and sandy loam (Al Kuisi et al, 2008).…”
Section: Methodology Study Areamentioning
confidence: 99%
“…Fruit trees and palms are grown in the Al Remal and Muaddi areas. Soil texture in the study area is mainly clay loam, loam, silt loam, and sandy loam (Al Kuisi et al, 2008).…”
Section: Methodology Study Areamentioning
confidence: 99%
“…The study of methods for fitting filtration devices with extractants is beginning to be initiated, but stability and efficiency are difficult to take into consideration simultaneously [ 8 ]. Many experts have also begun to investigate new structures to overcome previous defects to improve system stability and collection efficiency [ 9 , 10 , 11 ]. It has been suggested that microfiltration bodies as supporting elements, with the addition of various chemical reactions in combination with organophosphate liquids, can efficiently overcome the problem of microfiltration carrier leakage.…”
Section: Introductionmentioning
confidence: 99%
“…The migration effect of traditional water treatment methods is not good. This study attempts to explore the method of extracting praseodymium, which provides theoretical support for the treating of praseodymium sewage in the future [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%